Radioisotope Renography During Furosemide (Lasix) Diuresis - Radó, J. P.; Bános, Cs.; Takó, J. (Nuklearmedizin - NuclearMedicine, 1968)
In 20 selected patients isotope renography was done in dehydration and during diuresis induced by the administration of furosemide (Lasix). In 19 patients a significant disparity between the tracings of the two kidneys was found in the dehydration renogram. The disparity disappeared during furosemide diuresis in patients with mild ureteropelvic obstruction, different forms of hypertension, pyelonephritis but without substantial loss of functioning renal mass. In five cases in which intravenous pyelography demonstrated significant differences in size between the two kidneys, the disparity between the tracings in the control renogram did not change substantially during furosemide diuresis. Furosemide diuresis seemed to be helpful in the evaluation of apparently abnormal renograms. The “furosemide renogram” may, in selected patients, be advantageous in isotope renography involving high diuresis.